2020
DOI: 10.1111/ijcp.13948
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patients’ diagnoses in a dermatology outpatient clinic during the COVID‐19 pandemic period and pre‐pandemic period

Abstract: Aim In this study, we compared the current diagnoses of patients admitted to the dermatology outpatient clinic with the diagnoses during the non‐pandemic period, and we examined the effect of COVID‐19 on the patient profile. Methods Diagnoses were compared by examining the patient files of the 3‐month period when the pandemic was influential in our country and the 2‐week non‐pandemic period corresponding to the same season a year ago. The outpatient diagnoses in the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 15 publications
(34 reference statements)
3
30
4
Order By: Relevance
“…Therefore, the decrease in polymorphic light eruption may be attributable to the lack of type 4 allergic reaction pattern. In contrast to the presented study, Turkmen et al (13) reported high polymorph light eruption, and this was attributable to seasonal factors.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, the decrease in polymorphic light eruption may be attributable to the lack of type 4 allergic reaction pattern. In contrast to the presented study, Turkmen et al (13) reported high polymorph light eruption, and this was attributable to seasonal factors.…”
Section: Discussioncontrasting
confidence: 99%
“…This result may be expected, with the increase in the time that families spend together at home. Similar results in other studies support this finding (8,9,13,18). In addition, a decrease in telogen effluvium cases was observed, which is the most common disease in dermatology outpatient clinics.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…11 Regarding scabies, a Spanish study reported the unexpected finding a crude increase in the number of cases during the national lockdown, 12 and other studies also reported an increase in the scabies 'frequency'. [13][14][15] However, these studies also reported an increase in the frequency of many other severe or disabling dermatological conditions, which can probably be explained by a dramatic decrease in the total number of dermatological consultations for benign conditions during the pandemic.…”
Section: Discussionmentioning
confidence: 96%
“…In a study conducted in Turkey, it was reported that scabies increased during the pandemic, the rates of which increased more at month three compared to month one following the first case of COVID‐19 16 . It is thought that domestic transmission due to staying at home policy also contributed to this result.…”
Section: Discussionmentioning
confidence: 99%